2005
DOI: 10.1103/physrevlett.95.177601
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Behavior of the Ferroelectric Polarization inPbTiO3/SrTiO3Superlattices

Abstract: Artificial PbTiO3/SrTiO3 superlattices were constructed using off-axis RF magnetron sputtering. X-ray diffraction and piezoelectric atomic force microscopy were used to study the evolution of the ferroelectric polarization as the ratio of PbTiO3 to SrTiO3 was changed. For PbTiO3 layer thicknesses larger than the 3-unit cells SrTiO3 thickness used in the structure, the polarization is found to be reduced as the PbTiO3 thickness is decreased. This observation confirms the primary role of the depolarization field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
188
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(197 citation statements)
references
References 34 publications
(46 reference statements)
8
188
1
Order By: Relevance
“…The average polarization can exceed the bulk polarization of the ferroelectric component [1], providing a new route for the enhancement of functional properties including piezoelectricity. This average polarization and structural evidence for a static polarization in the non-ferroelectric layers have been observed experimentally [5,6]. The desirable functional properties of unit-cell-scale superlattices, however, are defined by their responses to applied fields including mechanical stress and electric fields, and have yet to be fully exploited.…”
mentioning
confidence: 99%
“…The average polarization can exceed the bulk polarization of the ferroelectric component [1], providing a new route for the enhancement of functional properties including piezoelectricity. This average polarization and structural evidence for a static polarization in the non-ferroelectric layers have been observed experimentally [5,6]. The desirable functional properties of unit-cell-scale superlattices, however, are defined by their responses to applied fields including mechanical stress and electric fields, and have yet to be fully exploited.…”
mentioning
confidence: 99%
“…The ferroelectrics were all tetragonal ͑001͒-oriented, epitaxial thin films grown by rf-magnetron sputtering on conducting Nb: SrTiO 3 substrates, allowing the polarization to be switched along the c-axis perpendicular to the plane of the film. Different materials, including PbTiO 3 − SrTiO 3 superlattices, 8 PbZr 0.2 Ti 0.8 O 3 , PbTiO 3 , and BaTiO 3 were investigated to test their response to the high temperatures ͑700-1040°C͒ and reducing atmosphere required for CNT growth. All Pb-containing oxides showed increased surface roughness and significant deterioration of ferroelectric properties.…”
mentioning
confidence: 99%
“…8 The direct relation between tetragonality and polarization was also recently experimentally demonstrated in PbTiO 3 / SrTiO 3 superlattices. 12,13 In this letter, epitaxial c-axis PbTiO 3 thin films with thicknesses ranging from 480 Å down to 28 Å were grown on epitaxial La 0.67 Sr 0.33 MnO 3 electrodes ͑typically 200-300 Å thick͒ deposited onto ͑001͒ insulating SrTiO 3 substrates. It is found that the behavior of the tetragonality is dramatically different from what is observed for PbTiO 3 thin films prepared on metallic Nb-doped SrTiO 3 substrates, with an increase of c / a observed for the thinnest film studied.…”
mentioning
confidence: 99%